Phosphorus and Risk of Renal Failure in Subjects with Normal Renal Function - Sim, John J.; Bhandari, Simran K.; Smith, Ning; Chung, Joanie; Liu, In Lu A.; Jacobsen, Steven J.; Kalantar-Zadeh, Kamyar (The American journal of medicine, 2013)
Whether higher serum phosphorus levels increase risk for kidney disease onset and progression to end-stage renal disease in those with normal renal function is largely unknown. We sought to determine whether higher serum phosphorus levels increase risk for end-stage renal disease within a large ethnically diverse population with normal kidney function. A retrospective longitudinal cohort study was performed in the period January 1, 1998 through December 31, 2008 of adults within a vertically integrated health plan (3.4 million members). The primary objective was to determine risk of incident end-stage renal disease. Baseline and time-averaged phosphorus were used for Cox regressions analyses to calculate hazard ratios (HR) adjusting for age, sex, race, pre-existing hypertension, and diabetes. A total of 94,989 subjects were identified in the 11-year observation period. Mean age of the cohort was 50 years, with 61% female, 38% white, 14% black, and 25% Hispanic. Population-based phosphorus quartile ranges were 1.9-3.0 mg/dL, 3.1-3.4 mg/dL, 3.5-3.8 mg/dL, and 3.9-5.7 mg/dL. End-stage renal disease occurred in 130 (0.1%) subjects. Every 0.5-mg/dL phosphorus increase demonstrated an adjusted HR of 1.40 (95% confidence interval [CI], 1.06-1.84) and HR for mortality of 1.09 (95% CI, 1.06-1.13). Adjusted HRs were 0.64 (95% CI, 0.37-1.11), 0.83 (95% CI, 0.50-1.39), and 1.48 (95% CI, 0.96-2.28) in the 2nd, 3rd, and 4th quartile, respectively, compared with the first phosphorus quartile. Time-averaged serum phosphorus demonstrated a similar relationship across quartiles and as a continuous variable. In our large, ethnically diverse cohort of non kidney disease subjects, higher serum phosphorus levels were associated with greater risk for end-stage renal disease and mortality.